2016
DOI: 10.1111/nyas.13279
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and neural activation in adults with β‐thalassemia major: an event‐related potentials study

Abstract: In recent years, there has been growing interest in understanding the involvement of the nervous system and neurological complications in β-thalassemia major (β-TM). Several reports have demonstrated β-TM-related neurological abnormalities, and these have been postulated to be responsible for impaired cognitive and neuropsychological functioning. We investigated neural correlates of cognitive function in adults with β-TM and healthy controls using scalp-recorded event-related potentials (ERPs). To date, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 57 publications
(102 reference statements)
3
16
0
Order By: Relevance
“…β‐TM patients exhibited augmentation of P1 and N1 and P3 amplitudes to Go stimuli and P1, N2 and P3 amplitudes to Stop stimuli than healthy controls. This is in line with our other study, which also found P1 and N1 augmentation in β‐TM patients, despite the use of a different task with different cognitive demands (Raz et al , ). A possible interpretation of the present results is that β‐TM patients need to recruit additional brain resources, relative to healthy individuals, when dealing with cognitive challenge, such as the stop‐signal task.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…β‐TM patients exhibited augmentation of P1 and N1 and P3 amplitudes to Go stimuli and P1, N2 and P3 amplitudes to Stop stimuli than healthy controls. This is in line with our other study, which also found P1 and N1 augmentation in β‐TM patients, despite the use of a different task with different cognitive demands (Raz et al , ). A possible interpretation of the present results is that β‐TM patients need to recruit additional brain resources, relative to healthy individuals, when dealing with cognitive challenge, such as the stop‐signal task.…”
Section: Discussionsupporting
confidence: 93%
“…The present study is part of a series of studies aimed at examining neural correlates of cognitive function in adults with TDT β‐TM using the ERP technique. We have recently found that impaired task switching ability is associated with early ERPs alterations among adult patients (Raz et al , ). In the present study we sought to identify behavioural and brain correlates of attention and response inhibition functions by using a stop‐signal task in which participants have to quickly and effectively respond to frequent Go stimuli while withholding their response when a Go stimulus is immediately followed by a stop sign.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The exposure of phosphatidylserine on red blood cells is highly associated with the expression of platelet activation markers. Red blood cells exposed to phosphatidylserine may also directly cause the vascular damage detected in thalassemia (5).…”
Section: Introductionmentioning
confidence: 99%